SHOCK ABSORBER - YAMASHITA Mikio (2022)
This shock absorber has a first damping force characteristic when a piston speed is from a low-speed region to a high-speed region while a relative position of a piston (18) in relation to a cylinder (2) at low frequencies is in a first range, and has a second damping force characteristic greater than the first damping force characteristic when the piston speed is from a low-speed region to a high-speed region while the relative position at low frequencies is in a second range different from the first range. A second passage (181) is provided with a variable orifice mechanism (325) of which the orifice area can be changed according to the relative position, and a frequency-sensitive mechanism (43) in which the damping force at low frequencies is higher than the damping force at high frequencies irrespective of the piston speed, so that, at high frequencies, the difference in damping force characteristic between the first range and the second range is smaller than the difference between the first damping force characteristic and the second damping force characteristic. Cet amortisseur présente une première caractéristique de force d'amortissement lorsqu'une vitesse de piston passe d'une région à faible vitesse à une région à grande vitesse tandis qu'une position relative d'un piston (18) par rapport à un cylindre (2) à basses fréquences se trouve dans une première plage, et présente une seconde caractéristique de force d'amortissement supérieure à la première caractéristique de force d'amortissement lorsque la vitesse de piston passe d'une région à faible vitesse à une région à grande vitesse tandis que la position relative à basses fréquences se trouve dans une seconde plage différente de la première plage. Un second passage (181) est pourvu d'un mécanisme à orifice variable (325) dont la zone d'orifice peut être modifiée en fonction de la position relative, et d'un mécanisme sensible à la fréquence (43) dans lequel la force d'amortissement à basses fréquences est supérieure à la force d'amortissement à des fréquences élevées quelle que soit la vitesse du piston, de sorte que, à des fréquences élevées, la différence de caractéristique de force d'amortissement entre la première plage et la seconde plage est inférieure à la différence entre la première caractéristique de force d'amortissement et la seconde caractéristique de force d'amortissement. この緩衝器は、低周波時にシリンダ（２）に対するピストン（１８）の相対位置が第１範囲にある間は、ピストン速度が低速域から高速域まで、第１減衰力特性とし、低周波時に前記相対位置が第１範囲とは異なる第２範囲にある間は、ピストン速度が低速域から高速域まで、第１減衰力特性よりも大きい第２減衰力特性とし、高周波時には、第１範囲のときと第２範囲のときとの減衰力特性の差が、第１減衰力特性と第２減衰力特性との差よりも小さくなるよう、第２通路（１８１）には、前記相対位置によりオリフィス面積が変更可能な可変オリフィス機構（３２５）と、ピストン速度によらず、低周波時の減衰力が高周波時の減衰力よりも高くなる周波数感応機構（４３）と、が設けられている。